Auditor Workload and Its Implication on Auditor’s Professional Ability - Ely Suhayati (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The purpose of this study was to determine how much auditors’ workload can lead to dysfunctional auditors and how much dysfunctional auditors have implications on professional auditors’ ability. The method in this research is descriptive verification with the Structural Equation Modeling test as a tool in making conclusions. The sample in this study were 97 public accounting firms on Java island, with senior and junior public accountant observation units. The results of this study indicate that auditors’ workload accumulation will cause stress on auditors so that it triggers dysfunctionality and has an impact on decreasing auditors’ professional ability. In conclusion, the more the auditor’s workload, the more positive the auditor’s attitude. Besides, the lower the auditor’s dysfunctionality, the better the auditor’s professional skill. It indicates that an auditor will be able to tackle obstacles in the direction of advanced Indonesia.